An anthropology of futures and technologies - Lanzeni, Débora; Waltorp, Karen; Pink, Sarah 1966-; Smith, Rachel Charlotte (Routledge, 2023)
"This book examines emerging automated technologies and systems and the increasingly prominent roles that each plays in our lives and our imagined futures. It asks how technological futures are being constituted and the roles anthropologists can play in their making; how anthropologists engage with emerging technologies within their fieldwork contexts in research which seeks to influence future design; how to create critical and interventional approaches to technology design and innovation; and how a critical anthropology of the way that emerging technologies are experienced in everyday life circumstances offers new insights for future making practices. In pursuing these questions, this book respond to a call for new anthropologies that respond to the current and emerging technological environments in which we live, environments for which thinking critically about the possible, plausible, and impossible futures are no longer sufficient. Taking the next step, this book asserts that anthropology must now propose alternative ways, rooted in ethnography, to approach and engage with what is coming and to contest dominant narratives of industry, policy and government, and to respond to our contemporary context through a public, vocal and interventional approach"--
Keywords: Zukunft; Anthropologie; Prognose; Neue Technologie; Automation; Technological forecasting; Social prediction; Anthropology / Research; Future, The